A Highly Oxidizing and Isolable Oxoruthenium(V) Complex [RuV(N4O)(O)]2+: Electronic Structure, Redox Properties, and Oxidation Reactions Investigated by DFT Calculations. Issue 9 (20th June 2013) - Guan, Xiangguo; Chan, Sharon Lai‐Fung; Che, Chi‐Ming
Abstract The electronic structure and redox properties of the highly oxidizing, isolable RuVO complex [RuV(N4O)(O)]2+, its oxidation reactions with saturated alkanes (cyclohexane and methane) and inorganic substrates (hydrochloric acid and water), and its intermolecularcoupling reaction have been examined by DFT calculations. The oxidation reactions with cyclohexane and methane proceed through hydrogen atom transfer in a transition state with a calculated free energy barrier of 10.8 and 23.8 kcal mol−1, respectively. The overall free energy activation barrier (ΔG≠=25.5 kcal mol−1) of oxidation of hydrochloric acid can be decomposed into two parts: the formation of [RuIII(N4O)(HOCl)]2+ (ΔG=15.0 kcal mol−1) and the substitution of HOCl by a water molecule (ΔG≠=10.5 kcal mol−1). For water oxidation, nucleophilic attack on RuVO by water, leading to OO bond formation, has a free energy barrier of 24.0 kcal mol−1, the major component of which comes from the cleavage of the HOH bond of water. Intermolecular self‐coupling of two molecules of [RuV(N4O)(O)]2+ leads to the [(N4O)RuIVO2RuIII(N4O)]4+ complex with a calculated free energy barrier of 12.0 kcal mol−1.